2004
DOI: 10.1103/physrevb.69.075114
|View full text |Cite
|
Sign up to set email alerts
|

Fermi-surface analysis of a quasi-two-dimensional monophosphate tungsten bronze

Abstract: The P 4 W 8 O 32 compound is a member of the low-dimensional monophosphate tungsten bronzes family whose reduced dimensionality induces electronic instabilities such as charge-density waves ͑CDWs͒. We report here the direct mapping of the Fermi surface ͑FS͒ of this compound at room temperature using synchrotronradiation angle-resolved photoemission. The recorded FS images confirm the superimposition of three nested sheets, as proposed by the hidden-nesting model. We found two well defined parallel stripes alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…These materials are electronically more complex since the FS follows the so-called hidden nesting scenario [209], i.e., the FS results from the hybridization of three different one-dimensional FS. This study, while confirming the qualitative aspects of the eH calculations, has led to a better agreement with recent ARPES studies [210,211]. Calculation of precise FS (including interlayer interactions) and the associated Lindhard response function allowed an indepth discussion of the origin of the structural modulations occurring in these materials.…”
Section: Molybdenum and Tungsten Oxides And Bronzessupporting
confidence: 66%
“…These materials are electronically more complex since the FS follows the so-called hidden nesting scenario [209], i.e., the FS results from the hybridization of three different one-dimensional FS. This study, while confirming the qualitative aspects of the eH calculations, has led to a better agreement with recent ARPES studies [210,211]. Calculation of precise FS (including interlayer interactions) and the associated Lindhard response function allowed an indepth discussion of the origin of the structural modulations occurring in these materials.…”
Section: Molybdenum and Tungsten Oxides And Bronzessupporting
confidence: 66%
“…Thus, we study only the simplest model for pinned two-dimensional charge density waves with the characteristic wave vector Q = (π, π) on a square lattice. Although realistic two-dimensional CDW ordering usually takes place in more complicated situations 12,13,14 , the main conclusions of the present paper can be qualitatively applicable to them as well. Thus, if the nesting condition is valid only on a part of the Fermi surface, just respective electrons will participate in the density wave ordering and the Q-reflection will take place for respective region of momentum directions.…”
mentioning
confidence: 69%
“…The main question to answer at that moment was to what extent the undulation of the Fermi surface would indeed be compatible with a nesting mechanism, which requires flat areas in the Fermi surface. A comparison with well-known CDW compounds, such as NaMo 6 O 17 or KMo 6 O 17 , reveals that a large percentage of flat areas has always been required to stabilize a CDW [52][53][54][55][56]. In the case of Pb/Ge (111), it was concluded that both the theoretical and the experimental Fermi surfaces are undulated, but the fraction of flat areas is insufficient to obtain a significant energy gain associated with a CDW instability [25].…”
mentioning
confidence: 99%